Physical Condition Profile of Male Volleyball Athletes for the 2025 Magelang Regency Pre-Provincial Athletics Competition - Damar Adi Susetyo; Agung Wahyudi (Indonesian Journal for Physical Education and Sport, 2025)
This study aims to determine and analyze the physical condition profile of male volleyball athletes participating in the Magelang Regency Pre-PORPROV. The physical condition components analyzed include arm muscle strength, back muscle strength, leg muscle power, and cardiorespiratory endurance. The study used a quantitative approach with a survey method. The research subjects consisted of 14 male volleyball athletes from the Magelang Regency Pre-PORPROV team. The measurement instruments used were push-ups, back-ups, vertical jumps, and beep tests. Data analysis used a quantitative descriptive approach with normative categorization. The results showed that the overall physical condition profile of the male volleyball athletes of the Magelang Regency Pre-PORPROV team was in the moderate category (42.86%). Component analysis showed that arm muscle strength was in the good category (50%), back muscle strength was in the moderate category (42.86%), leg muscle power was in the moderate category (57.14%), and cardiorespiratory endurance was in the moderate category (35.71%). This study recommends a more structured training program with an emphasis on improving cardiorespiratory endurance and leg muscle power to maximize the athletes' performance in facing the PORPROV competition.